Starch-Glycerol Based Edible Film and Effect of Rosella (Hibiscus Sabdariffa Linn) Extract and Surimi Dumbo Catfish (Clarias gariepinus) Addition on Its Mechanical Properties - Endaruji Sedyadi; Syafiana Khusna Aini; Dewi Anggraini; Dian Prihatiningtias Ekawati (Biology, Medicine, & Natural Product Chemistry, 2016)
Effect of Rosella (Hibiscus Sabdariffa Linn) Extract and Surimi Dumbo catfish (Clarias gariepinus) addition on Starch-Based Edible Film-Glycerol Mechanical Properties has been done. The purpose of this study is to create an active environment-friendly packaging material. Surimi additions are intended to improve the mechanical properties of bioplastics and additions of Rosella extract intended as a bio-indicator of acidity. The method used was Solvent Casting. An amount of surimi and rosella extract varied to obtain the best mechanical properties. The results shows that the addition of surimi and rosella flower extract significantly effect the elongation of Edible films produced up to 27%.